The Effect of Chamomile Plant (Matericaria chamomile L.) As Feed Additives on Productive Performance, Carcass Characteristics and Immunity Response of Broiler - Mahmmod , Zhian A. (International Journal of Poultry Science, 2013)
This experiment was conducted to evaluate the effects of adding different levels of dried milled of chamomile flowers to broiler diets on productive performance, carcass characteristics and immune response of broiler. Two hundred fourty (Cobb) one day old chicks were used in this study. Chicks were weighted and randomly divided in to 4 treatments, with sixty birds/ treatment with 3 replicates 20 chicks of each. Chicks were fed the following diets. First group T1 control fed a basal diet while the T2, T3 and T4 groups were fed same diet as in the 1st group plus addition of 0.50, 1.00, 1.5 kg of chamomile flowers powder to (100kg) of diet. The experiment was lasted for 42 days. Birds were provided a three phase-feeding program (starter 3 weeks, grower 2 weeks and finisher one week). Birds and feed were weighed on 21, 35 and 42 day of age for growth performance, weight gain (WG), feed intake (FI), feed conversion ratio (FCR) and mortality rate were measured, at the end of experiment carcass quality (dressing %, breast% and giblets%) was measured and samples of blood were taken for measured immune response. Results showed that adding of Chamomile flowers at a level of 1 kg/100kg diet, T3 increased significantly (p<0.05). Live body weight (LBW), WG and FCR as compared with the control group and T2, and T4 groups at the 42 days of age, adding of chamomile flowers powder as a feed supplement with 0.5, 1.00, 1.5kg/100kg diet levels were significantly (p<0.05) decreased mortality as compared with control group. On the other hand all treatments revealed no significant differences on dressing percentage and giblets weight except thighs drumsticks, and heart weight increased significantly (p<0.05) in treatment T2. Adding of chamomile flowers with the above levels had no significant enhancement effect on antibody titers against Newcastle Disease Virus (NDV) and Infectious Bursal Disease (IBD) at 42 days of age.